2004
DOI: 10.1055/s-2004-821304
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Muscle Injuries by Local Administration of Autologous Conditioned Serum: A Pilot Study on Sportsmen with Muscle Strains

Abstract: Muscle injuries represent a major part of sports injuries and are a challenging problem in traumatology. Strain injuries are the most common muscle injuries after contusions. These injuries can lead to significant pain and disability causing time to be lost to training and competition. Despite the frequency of strain injuries the treatment available is limited and is generally not sufficient to enhance muscle regeneration efficiently when fast resumption of sport activity is a primary target. A number of growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
142
1
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(156 citation statements)
references
References 18 publications
2
142
1
10
Order By: Relevance
“…Over a decade ago, a pilot study was conducted among 18 professional sportsmen with moderate muscle strain injuries who were treated with ACS within 2 days of injury; injections were repeated every second day until complete recovery (mean treatments=5.4) [26]. ACS was prepared from patients' whole blood using a centrifugation technique that yielded significant increases in FGF-2 (750 %), TGF-B (31 %), HGF (hepatocyte growth factor) (35 %), and IL-1Ra (interleukin-1 receptor antagonist) (600 %).…”
Section: Clinical Studies Of Prp and Muscle Injurymentioning
confidence: 99%
“…Over a decade ago, a pilot study was conducted among 18 professional sportsmen with moderate muscle strain injuries who were treated with ACS within 2 days of injury; injections were repeated every second day until complete recovery (mean treatments=5.4) [26]. ACS was prepared from patients' whole blood using a centrifugation technique that yielded significant increases in FGF-2 (750 %), TGF-B (31 %), HGF (hepatocyte growth factor) (35 %), and IL-1Ra (interleukin-1 receptor antagonist) (600 %).…”
Section: Clinical Studies Of Prp and Muscle Injurymentioning
confidence: 99%
“…The authors concluded that PRP is helpful for decreasing pain in the immediate postinjury phase and may be helpful in facilitating early rehabilitation. Wright-Carpenter et al conducted a controlled trial where professional athletes with grade 2 or moderate muscle strains were treated with a series of autologous conditioned serum (ACS) [48]. Those in the ACS group had shorter time to return to sport (16.6 days compared to 22.3 days in control group), though this study is limited by lack of randomization and lack of blinding.…”
Section: Treatments To Enhance Return To Sports After Muscle Injurymentioning
confidence: 99%
“…Depuis une vingtaine d'années, plusieurs recherches in vitro ont permis de comprendre l'action plaquettaire en tant que médiateur ou activateur de la cicatrisation de différents tissus [8][9][10][11][12][13][14]. La réparation tissulaire se déroule classiquement selon trois étapes principales :…”
Section: Principe D'action Du Prpunclassified
“…Certains travaux, essentiellement in vitro, soulignent les propriétés réparatrices des plaquettes qui, effectivement, présentent la capacité d'accélérer la cicatrisation de différents tissus : os, muscles et tendons [8][9][10][11][12][13][14]. Le plasma enrichi en plaquettes (plateletrich plasma ou PRP) a déjà été utilisé en chirurgie maxillofaciale, en stomatologie ou en chirurgie orthopédique [9,10].…”
Section: Introductionunclassified